Passivity-Based Control Implementation Using Teensy 4.1 in Flywheel Energy Storage Systems with Wireless Power Flow Monitoring - Beni Satria (SEAN Institute, 2026)
This study implements Passivity-Based Control (PBC) on the Teensy 4.1 embedded platform for Flywheel Energy Storage System (FESS) equipped with wireless power flow monitoring. The objective of the study is to overcome the limitations of conventional controllers in handling nonlinear dynamics of FESS and integrate remote monitoring capabilities to support smart grid infrastructure. The research method uses an experimental approach by designing an Interconnection and Damping Assignment PBC (IDA-PBC) controller optimized for embedded computing limitations, implemented on Teensy 4.1 with a 10 kHz control loop. The system is integrated with an ESP32 wireless module for real-time data transmission to a remote dashboard. The results show that IDA-PBC is superior to Field-Oriented Control with an increase in rise time of 24.5%, settling time of 34.0%, overshoot of 74.4%, and disturbance rejection of 46.2%. Energy efficiency increases by 3.8% absolute (89.9% vs 86.1%) with lower total harmonic distortion. The implementation on Teensy 4.1 proved viable with 45.2% CPU utilization, while wireless monitoring achieved 18.5 ms latency and 0.12% packet loss. The contributions of this research include empirical validation of IDA-PBC on a real-world implementation, benchmarking of embedded platforms for nonlinear control, and demonstration of cyber-physical integration on FESS that supports the development of a more efficient and reliable smart grid.